Increased blaOXA-23-like prevalence in Acinetobacter baumannii at a tertiary care center in Lebanon (2007-2013) - Kanj, Souha S; Tayyar, Ralph; Shehab, Marwa; El-Hafi, Bassam; Rasheed, Sari S; Kissoyan, Kohar Annie Berge; Kanafani, Zeina A; Wakim, Rima Hanna; Kara Zahreddine, Nada; Araj, George F; Dbaibo, Ghassan; Matar, Ghassan M (The Journal of Infection in Developing Countries, 2018)
Introduction: Acinetobacter baumannii has become one of the most feared organisms in hospital-acquired infections during the past decades. Their multi-drug resistant profiles have rendered many broad-spectrum antibiotics ineffective. The purpose of this retrospective study is to describe and compare molecular characteristics of A. baumannii isolated from patients at a tertiary care center in Lebanon from two outbreaks, the first in 2007-2008 as part of a case-controlled study involving Acinetobacter baumannii cases admitted to the ICU and the second in 2013. Methodology: A total of 148 A. baumannii clinical isolates were collected from various clinical specimens during 2007-2008 and 2013. All A. baumannii isolates were subjected to PCR amplification of blaOXA-23-like and blaOXA-51-like genes of carbapenem resistance. Random amplification of polymorphic DNA (RAPD) was also performed to assess their genomic relatedness. Results: There was an increase in the prevalence of blaOXA-23-like and blaOXA-51-like between the two time periods; however, only with 22% genomic relatedness between 2007-2008 and 2013 isolates. Taking 80% as margin of compatibility, 31 distinct clusters containing 2 to 11 strains were observed in both time periods. Conclusion: The presence of numerous clusters accompanied by a predominant increase in the prevalence of blaOXA-23-like gene between 2007 and 2013 suggests a horizontal transmission of the gene within various strains of the species, constituting a primary factor in the continued increase of carbapenem resistance over the years. As such, infection control measures ought to be taken with the highest priority and compliance among all involved healthcare workers is of utmost importance.